PENERAPAN CORPORATE SOCIAL RESPONSIBILITY PADA BCA DAN BMI PERSPEKTIF EKONOMI ISLAM - Ulul Azmi Mustofa (ITB AAS INDONESIA, 2014)
The purpose of the thesis is to acknowledge the application of CSR in BCA Bank and BMI Bank period 2012, and what resources of fund are using in CSR programs, and to see Islamic economic about application CSR Bank BCA and Bank Muamamalat. This research is a qualitative research and research type is comparative research. The analyze that used are reduction method, data presentation and conclusion. This thesis concludes that the implementation of CSR in Bank BCA and Bank Muamalat there i he better from years to years. The application of CSR from philantropic to strategic. And than, resources of fund are using in CSR programs there is some resources, Bank BCA there is two resources. In other hand, Bank Muamalat there is some resources funds for implemetation of CSR. And than, In Perspective Islamic Economic, Islam Position in CSR Continuum, Implementation of CSR in Bank BCA is Strategic, and than implementation of CSR in Bank BMI is Taqwa-Centric.Key words: implementation, Corporate Social Responsibility, Islamic Economics a change for t